2016
DOI: 10.1007/s10811-016-1007-0
|View full text |Cite
|
Sign up to set email alerts
|

Thermostable phycocyanin from the red microalga Cyanidioschyzon merolae, a new natural blue food colorant

Abstract: The demand for natural food colorants is growing as consumers question the use of artificial colorants more and more. The phycobiliprotein C-phycocyanin of Arthospira platensis is used as a natural blue colorant in certain food products. The thermoacidophilic red microalga Cyanidioschyzon merolae might provide an alternative source of phycocyanin. Cyanidioschyzon merolae belongs to the order Cyanidiophyceae of the phylum Rhodophyta. Its natural habitat are sulfuric hot springs and geysers found near volcanic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 36 publications
0
37
0
2
Order By: Relevance
“…Likewise, the thermostable PC from the Synechococcus lividus PCC 6715 strain that was isolated from a hot spring maintained 90% and 70% stability at 50 • C for 5 h and two weeks, respectively [45]. Additionally, PC from the thermophilic red algae Cyanidioschyzon merolae showed a midpoint denaturation at 83 • C and pH 5, with a half-life of 40 min [46].…”
Section: Pbps Stability Under Different Temperature Regimesmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the thermostable PC from the Synechococcus lividus PCC 6715 strain that was isolated from a hot spring maintained 90% and 70% stability at 50 • C for 5 h and two weeks, respectively [45]. Additionally, PC from the thermophilic red algae Cyanidioschyzon merolae showed a midpoint denaturation at 83 • C and pH 5, with a half-life of 40 min [46].…”
Section: Pbps Stability Under Different Temperature Regimesmentioning
confidence: 99%
“…Gravid worms were gently shaken at room temperature in 10 volumes of a fresh 1% NaClO/0.5 M NaOH solution. Carcasses and other debris were dissolved after 5-10 min, and resistant eggs (50% to 100% viable eggs) were collected and washed several times in an M-9 buffer [46]. The M-9 buffer was prepared with 1.5 g of KH 2 PO 4 , 3.0 g of Na 2 HPO 4 , 2.5 g of NaCl, 0.5 mL of 1 M MgSO 4 , and sterile distilled water to a final volume of 500 mL [68].…”
Section: Toxicity Assaysmentioning
confidence: 99%
“…Phycocyanin is a phycobiliprotein pigment with a bright blue colour that is used as a natural colourant in various sweets and drinks . Demand for phycocyanin has increased in recent years because synthetic colourants are increasingly being replaced by natural colourants in the food industry, mostly due to real or perceived negative health effects of synthetic colourants . Phycocyanin may even have positive health effects because it possesses antioxidant, anticancer, neuroprotective and anti‐inflammatory properties …”
Section: Introductionmentioning
confidence: 99%
“…Phycocyanin is a blue pigment with absorbance wavelengths of 500 and 550 nm (Eriksen, 2008). In this study, the pigment was only present in ethanol extracts of two green algae; U. reticulata and C. viellardi, although Rahman et al (2017) reported the presence of phycocyanin in Cyanidioschyzon merolae, a red algae. The presence of carotenoids in acetone extract of R. grande is consistent with the findings reported by Yoshii et al (2004), who also extracted carotenoids from the genus, Rhizoclonium.…”
Section: Discussionmentioning
confidence: 57%